2008
DOI: 10.1002/zamm.200700131
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of a magneto‐sensitive elastic sphere

Abstract: Magneto-sensitive (MS) or magnetorheological (MR) elastomers are smart materials whose mechanical properties change instantly by the application of a magnetic field. MS elastomers are widely used in the practice as elements of MEMS (sensors, actuators, etc.), for example, in medical devices. The behavior of MS elastomers under time-dependent magnetic field is a complex process and till now is not investigated in all details. Here we present the statements of the dynamic boundary-value problem of a MS elastomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Here ... denotes the integration over the plate thickness h. For the plate which is symmetrically to the midplane the relation B B B = 0 0 0 holds true. The relaxation functions of the isotropic viscoelastic plate with symmetric cross-section were considered in [25]. Note that for the isotropic viscoelastic material three functions E(s), µ(s) and ν(s) are introduced.…”
Section: Advances In Strength Of Materialsmentioning
confidence: 99%
“…Here ... denotes the integration over the plate thickness h. For the plate which is symmetrically to the midplane the relation B B B = 0 0 0 holds true. The relaxation functions of the isotropic viscoelastic plate with symmetric cross-section were considered in [25]. Note that for the isotropic viscoelastic material three functions E(s), µ(s) and ν(s) are introduced.…”
Section: Advances In Strength Of Materialsmentioning
confidence: 99%
“…For sandwich shells containing ER/MR core, there are only a few results, see, for example, Yeh (2011), Mohammadi and Sedaghati (2012), Mikhasev et al (2011Mikhasev et al ( , 2014 and Altenbach et al (2008). Yeh (2011) and Mohammadi and Sedaghati (2012) developed different variants of FEM to analyse free vibrations of sandwich shells containing ER core and shown that applying electric fields leads to both the change of eigenfrequencies and enhancement of damping properties of smart structures.…”
Section: Introductionmentioning
confidence: 99%
“…They formulated general asymptotic solutions of the three-dimensional equations of magnetoelasticity for shells and plates and proposed a theory of magnetoelasticity for thin bodies. Wave propagations, oscillations, control and other problems in the theory of magnetoelastic solids are considered in [2,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%